Bury your dead - Penny, Louise (Penny, Louise. Three Pines mystery., 2010)
As Quebec City shivers in the grip of winter, its ancient stone walls cracking in the cold, Chief Inspector Armand Gamache plunges into the strangest case of his celebrated career. A man has been brutally murdered in one of the city's oldest buildings - a library where the English citizens of Quebec safeguard their history. And the death opens a door into the past, exposing a mystery that has lain dormant for centuries . . . a mystery Gamache must solve if he's to catch a present-day killer.